The Effect of Physical Activity during Pregnancy on Childbirth - Al Hassan, Raya; Ali, Ria Rashid; Alsheikh, Mariam Saad Kaiss (Open Access Macedonian Journal of Medical Sciences, 2022)
Active pregnant women have fewer physical problems and gain weight during pregnancy, and this often leads to fewer complications as exercise also increases self-confidence and reduces the risk of mood swings after childbirth (postpartum) and depression, and “it is not only the women who benefits from being active.” Studies have shown that exercise during pregnancy has a “training effect” on the baby, and this is reflected in increased heart rate variability and a decrease in the fetus’s resting heart rate. Aim of this study is known Effect of Physical Activity during Pregnancy on Childbirth. 155 patients were collected from Bint Al-Huda Maternity & Children Hospital, Thi-Qar, Iraq, and the samples were divided into two groups (90 women who practiced exercise and 65 for control). All demographic information about patients was obtained through the distribution of questionnaires, and several techniques were used to analyze the results, including the statistical analysis program in evaluating physical activity on childbirth and analyzing the effects generated during pregnancy and the duration of the stage of labor and Positive results were found in the assessment of physical activity on pregnant women, and the results were in another way related to age and body mass index.